Critical current density of high-temperature superconducting ceramics BSCCO Bi-2223 - Uskenbaev, D.E.; Nogai, A.S.; Uskenbayev, A.D.; Nogai, E.A.; Kudussov, A.S.; Khamzina, B.E. (Bulletin of the Karaganda University. “Physics” Series., 2024)
In the paper the results of the study on the synthesis of high-temperature superconducting ceramics of nomi-nal composition Bi1.6Pb0.4Sr2Ca2Cu3Oy by various methods were presented based on amorphous phases using glass-ceramic technology and solid-phase method. For comparison, amorphous phases were obtained in two ways. In the first case, a heating furnace of a special design was developed to obtain an amorphous phase, which provides melting without using a crucible. The heating of the initial samples for melting is carried out due to the combined effect of the convection heat flux and the radiation of heating elements, which consists of the IR region of the spectrum at a melting temperature in the spectral range of 1300–1350 nm. In the se-cond case, melting is carried out under the influence of broadband optical radiation, including UV, visible and IR spectral regions. The production of glassy precursors is carried out by draining the melt onto a quenching device in the form of a propeller made of stainless steel. Studies of the formation rate of the superconducting high-temperature phase Bi-2223 were carried out in the same temperature conditions at 848–850 °C with in-termediate grinding every 24 hours and the study of the phase composition by X-ray diffraction method. Studies showed that the glass phase-based method ensures the completeness of the formation of the high-temperature phase Bi-2223 and the rate of its formation is significantly higher than by the solid-phase method (2.5–3 times). Studies of the critical density of the transport current have shown that the current value is 7.05×103 mA/cm2, (measured by the criterion of 1 μV/cm), which is significantly higher compared to other methods.
Keywords: superconductivity; glass phase; microstructure; ceramics; IR radiation; diffractogram; melt; crys-tallization